Accidental breaches of the doping regulations in sport: is there a need to improve the education of sportspeople? - Somerville, S. J.; Lewis, M. (British Journal of Sports Medicine, 2005)
Objectives: To identify educational needs of elite sportspeople with respect to the doping laws.